2017
DOI: 10.1016/j.ijbiomac.2016.10.061
|View full text |Cite
|
Sign up to set email alerts
|

A new TRAF-like protein from B. oleracea ssp. botrytis with lectin activity and its effect on macrophages

Abstract: Lectins are involved in a wide range of biological mechanisms, like immunomodulatory agent able to activate the innate immunity. In this study, we purified and characterized a new lectin from cauliflower (Brassica oleracea ssp. botrytis - BOL) by three sequential chromatographic steps and confirmed the purity by SDS-PAGE. Additionally, we evaluated the role of the lectin in innate immunity by a phagocytosis assay, production of HO and NO. BOL was characterized like a non-glycosylated protein that showed a mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…The results showed that SteLL induced the the release of cytokines (IL-6, IL-10, IL-17A, and TNF-α) and reactive species (nitric oxide, superoxide anion) by uninfected macrophagens. The ability of plant lectins to alter the macrophage responses have been demonstrated by other authors 18,19,53 . The effects of SteLL on nitric oxide and superoxide anion production may be related to the improvement of macrophages bactericidal action, since these reactive species play essential roles in the defense against infectious diseases 54,55 .…”
Section: Discussionmentioning
confidence: 68%
“…The results showed that SteLL induced the the release of cytokines (IL-6, IL-10, IL-17A, and TNF-α) and reactive species (nitric oxide, superoxide anion) by uninfected macrophagens. The ability of plant lectins to alter the macrophage responses have been demonstrated by other authors 18,19,53 . The effects of SteLL on nitric oxide and superoxide anion production may be related to the improvement of macrophages bactericidal action, since these reactive species play essential roles in the defense against infectious diseases 54,55 .…”
Section: Discussionmentioning
confidence: 68%
“…Ensaios preliminares mostraram que a fagocitose e a produção NO por macrófagos foram estimuladas na presença de BOL, o que demonstra a possibilidade dessa lectina atuar como agente imunoestimulador capaz de auxiliar na ativação da imunidade inata (Duarte et al 2017). Entretanto, a quantidade de proteína nativa recuperada no processo de purificação limita o número de ensaios biológicos que podem ser realizados.…”
Section: Introductionunclassified